Unveiling the antitumor potential of novel N-(substituted-phenyl)-8-methoxycoumarin-3-carboxamides as dual inhibitors of VEGFR2 kinase and cytochrome P450 for targeted treatment of hepatocellular carcinoma - Eman M. Radwan; Eman Abo-Elabass; Atef E. Abd El-Baky; Hussah Abdullah Alshwyeh; Hussah Abdullah Alshwyeh; Riyad A. Almaimani; Ghassan Almaimani; Ibrahim Abdel Aziz Ibrahim; Abdulaziz Albogami; Mariusz Jaremko; Samar Z. Alshawwa; Essa M. Saied; et al. (Frontiers in Chemistry, 2023)
Being the sixth most diagnosed cancer and the fourth leading cause of cancer-related deaths worldwide, liver cancer is considered as a serious disease with a high prevalence and poor prognosis. Current anticancer drugs for liver cancer have drawbacks, such as limited efficacy in later stages of the disease, toxicity to healthy cells, and the potential for drug resistance. There is ample evidence that coumarin-based compounds are potent anticancer agents, with numerous analogues currently being investigated in preclinical and clinical studies. The current study aimed to explore the antitumor potency of a new class of 8-methoxycoumarin-3-carboxamides against liver cancer. Toward this aim, we have designed, synthesized, and characterized a new set of N-(substituted-phenyl)-8-methoxycoumarin-3-carboxamide analogues. The assessment of antitumor activity revealed that the synthesized class of compounds possesses substantial cytotoxicity toward Hep-G2 cells when compared to staurosporine, without significant impact on normal cells. Out of the synthesized compounds, compound 7 demonstrated the most potent cytotoxic effect against Hep-G2 cells with an IC50 of 0.75 µM, which was more potent than the drug staurosporine (IC50 = 8.37 µM). The investigation into the mechanism behind the antiproliferative activity of compound 7 revealed that it interferes with DNA replication and induces DNA damage, leading to cell cycle arrest as demonstrated by a significant decrease in the percentage of cells in the G1 and G2/M phases, along with an increase in the percentage of cells in the S phase. Flow cytometric analysis further revealed that compound 7 has the ability to trigger programmed cell death by inducing necrosis and apoptosis in HepG-2 cells. Further explorations into the mechanism of action demonstrated that compound 7 displays a potent dual-inhibitory activity toward cytochrome P450 and vascular endothelial growth factor receptor-2 (VEGFR-2) proteins, as compared to sorafenib drug. Further, detailed computational studies revealed that compound 7 displays a considerable binding affinity toward the binding cavity of VEGFR2 and CYP450 proteins. Taken together, our findings indicate that the newly synthesized class of compounds, particularly compound 7, could serve as a promising scaffold for the development of highly effective anticancer agents against liver cancer.